0400 Predictors Of Initiation And Attendance In Cognitive-Behavioral Therapy For Insomnia (CBT-I) Among Latina And Non-Latina Caucasian Pregnant Women. (27th April 2018) - Rangel, E; Simpson, N; Asarnow, L; Manber, R
Abstract: Introduction: Cognitive behavioral therapy for insomnia (CBT-I) has been shown to be effective in the general population, but little is known about the use of CBT-I among underserved populations. Previous studies have shown that people of Latino ethnicity are less likely to engage in mental health interventions. Here, we focus on treatment initiation and attendance among Latina and non-Latina pregnant women in a randomized controlled trial of CBT-I. Methods: Participants were Latina (mean age=32.03 ± 5.60 years, n=62) and non-Latina Caucasian pregnant women (mean age=32.98 ± 4.74 years, n=67) with insomnia disorder who were enrolled in a randomized controlled trial of CBT-I. The Insomnia Severity Index (ISI) and Edinburgh Postnatal Depression Scale (EPDS) were administered at screening. Results: A logistic regression demonstrated that Latina ethnicity was a significant predictor of non-initiation of treatment (no sessions attended) after adjusting for ISI, EPDS, working status, and parity (β= -2.45, p =.03, n=129). No other factors in the model were significant predictors. For the number of sessions attended after initiation, an independent samples t-test found that Latina women attended fewer sessions (M=4.4, SD=1.2, n=50) than Non-Latina Caucasian women (M=4.7, SD=0.7, n=66; t (114)=-1.98, p =.05). However, in a regression analysis adjusting for ISI and EPDS and including working status and parity, ethnicity was not a significant predictor of fewer sessions attended, F(5, 109)=1.04, p =.40. Conclusion: In a randomized controlled trial of CBT-I, Latina pregnant women with insomnia had a significantly lower likelihood of initiating treatment, but were equally likely to stay in treatment once they began. Focused research on identifying and reducing barriers to engagement in CBT-I among Latinx populations is a critical step to increase access to treatment among this underserved population. Support (If Any): NR013662.